Politics, Disability Governance and Inclusiveness of Parasport Athletes in a Coronavirus Pandemic Aftermath in Africa: Observations from Nigeria - Okudolo, P.T.I.; Ojakorotu, V. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
The paper evaluates politics and governance underlining disability inclusion development using reflections in parasport. Its thesis-of-thesis derives from the presentation of surveyed explanations from Nigerian stakeholders in the Paralympics sector to generalize for Africa. Before the COVID-19 pandemic outbreak, politics in Africa shows an abysmal scorecard in terms of combating discrimination against disabled persons. Accordingly, the continent's disability inclusiveness governance shows it is effectual. Thus, there is perhaps ample indication to adduce that sports politics will continually fail to achieve the inclusiveness of parasports athletes in a coronavirus epidemic aftermath. Using the Nigerian context, the paper gathers evidence from interviews with stakeholders and evaluative-secondary data in parasports concerning not only to responding to disability inclusion in sports but also to the wider politics of sustaining inclusiveness of Paralympic athletes in a post-COVID-19 era. The paper argues that the character of politics in Africa generally has not resulted in optimal investments, considerations, and willpower from political leaders to advance outcomes in the aspect of inclusivity of athletes with disabilities. It considers contextual factors that militate against achieving all-inclusiveness of disabled sports persons and how politics can be channelled to achieve their optimum well-being in the sports arena.